Common mechanisms in pediatric acute liver failure - Mann, Jake P.; Lenz, Dominic; Stamataki, Zania; Kelly, Deirdre (Trends in molecular medicine, 2023)
Acute liver failure (ALF) is a rare but potentially fatal disease in children. The etiology is multifactorial, including infection, autoimmune, and genetic disorders, as well as indeterminate hepatitis, which has a higher requirement for liver transplantation. Activation of the innate and adaptive immune systems leads to hepatocyte-specific injury which is mitigated by T regulatory cell activation. Recovery of the native liver depends on activation of apoptotic and regenerative pathways, including the integrated stress response (ISR; e.g., PERK), p53, and HNF4α. Loss-of-function mutations in these pathways cause recurrent ALF in response to non-hepatotropic viruses. Deeper understanding of these mechanisms will lead to improved diagnosis, management, and outcomes for pediatric ALF.